REPRESENTASI PELECEHAN TERHADAP KIAI DALAM MEDIA TELEVISI NASIONAL: ANALISIS ADAB ISLAM PERSPEKTIF AL-QUR’AN DAN TEORI REPRESENTASI STUART HALL - Luthviyah Romziana; Zaimuddin; Moh. Najiburrahman; Babun Suharto (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The phenomenon of harassment of kiai in a Trans7 broadcast on October 13, 2025, indicates a serious problem in religious ethics and public communication. As a figure of ulama and guardian of community morals, kiai holds a central position in the Nusantara Islamic tradition, so that respect for him is part of Islamic etiquette based on the values ​​of the Qur'an. This study aims to analyze media representations of kiai figures and examine how the principles of Islamic etiquette can become a framework for criticism of communication practices that demean the dignity of ulama. The method used is descriptive qualitative through content analysis and maudhu'i interpretation of Quranic verses on the ethics of speaking, respect for ulama, and social ethics, combined with Stuart Hall's representation theory. The results show that the media encoding process reflects the logic of entertainment capitalism that normalizes jokes about kiai. Meanwhile, audience decoding is divided into three positions: dominant, negotiating, and opposition. The Qur'anic perspective assesses that this practice is contrary to the principles of etiquette in QS. Al-Baqarah: 83, QS. Al-Ahzab: 70, and QS. Al-Hujurat: 2, 6, 11. This study emphasizes the importance of Qur'anic ethics as a critical paradigm in building a civilized media culture and maintaining the dignity of scholars.